2015
DOI: 10.1002/jpln.201400535
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon, nitrogen, and phosphorus distribution in stable aggregates of an Ultisol under contrasting land use and management history

Abstract: Different land-use affects the organization of mineral soil particles and soil organic components into aggregates and the consequent arrangement of the aggregates will influence essential ecosystem functions. We investigated a continuous rubber plantation (forested), land fallowed for 10 y (fallow), 10-y continuous arable cropping land and cropped land with top soil removed (TSR) for concentrations of C, N, and P in bulk soil and dry aggregates. Results showed that a high level of soil disturbance decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 24 publications
10
28
1
Order By: Relevance
“…I.e., adding lignohumate into compost reduced the decrease in the stability of soil aggregates (N50 + K; N50 + C), in comparison with the variants fertilized only with mineral fertilizer. The same phenomenon was observed in the study of Udom (2015). However, variant N100 + C did not reveal improvement of the stability of soil aggregates.…”
supporting
confidence: 84%
“…I.e., adding lignohumate into compost reduced the decrease in the stability of soil aggregates (N50 + K; N50 + C), in comparison with the variants fertilized only with mineral fertilizer. The same phenomenon was observed in the study of Udom (2015). However, variant N100 + C did not reveal improvement of the stability of soil aggregates.…”
supporting
confidence: 84%
“…Notably, P has a relatively closed cycle, with most of the mineralized and dissolved P from microaggregates adsorbed onto unaggregated clay-sized particles (< 53 μm) or utilized by plants [26]. Reportedly, some studies have shown that the soil aggregate stability and size affect the soil P distribution [27][28][29]. Higher percentages of both waterextractable and Mehlich III-extractable P were observed in both the 0.50-0.25 and 0.25-0.125 mm aggregate fractions [30].…”
Section: Introductionmentioning
confidence: 99%
“…This is because organic litter fall from the cassava may have contributed to lower the soil bulk density. Kou et al (2012) and Udom and Ogunwole (2015) have agreed that, the volume of organic matter in the soil usually improved soil structure and consequently, the bulk density. Total porosity and permeability of the soils were higher in cassava and plantain soils, an indication of great input of organic residues which enhanced these soil physical properties.…”
Section: Discussionmentioning
confidence: 84%
“…This method can provide useful information on SOC dynamics under natural conditions or short-term management practices (Shrestha et al, 2007). Previous research has indicated that changes in land use (or management practices) have a marked impact on the amount of Organic Carbon (OC) in particle-size fractions, which could serve as an early indicator to identify the impact of land-use change on SOC storage (Leifeld and Kogel-Knabner, 2005;Udom and Ogunwole, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation